Description of the Serological Response After Treatment of Chronic Imported Schistosomiasis - Marta González-Sanz; Irene Martín-Rubio; Oihane Martín; Alfonso Muriel; Sagrario de la Fuente-Hernanz; Clara Crespillo-Andújar; Sandra Chamorro-Tojeiro; Begoña Monge-Maíllo; Francesca F. Norman; José A. Pérez-Molina (Tropical Medicine and Infectious Disease)
Background: Chronic schistosomiasis can lead to significant morbidity. Serology is highly sensitive; however, its role in assessing treatment response is controversial. This study aimed to analyze serological values following treatment of chronic imported schistosomiasis. Methods: A retrospective observational study was performed including patients treated for chronic imported schistosomiasis from 2018 to 2022 who had at least one serological result at baseline and during follow-up. Demographic, clinical, and laboratory data were evaluated. Generalized estimating equation (GEE) models and Kaplan–Meier curves were used to analyze the evolution of serological values. Results: Of the 83 patients included, 72 (86.7%) were male, and the median age was 26 years (IQR 22–83). Most patients, 76 (91.6%), were migrants from sub-Saharan Africa. While 24 cases (28.9%) presented with urinary symptoms, the majority (59; 71.1%) were asymptomatic. Schistosoma haematobium eggs were observed in five cases (6.2%). Eosinophilia was present in 34 participants (40.9%). All patients had an initial positive Schistosoma ELISA serology, median ODI 2.3 (IQR 1.5–4.4); the indirect hemagglutination (IHA) test was positive/indeterminate in 34 cases (43.1%). Following treatment with praziquantel, serology values significantly decreased: −0.04 (IC95% −0.073, −0.0021) and −5.73 (IC95% −9.92, −1.53) units per month for ELISA and IHA, respectively. A quarter of patients (25%) had negative ELISA results 63 weeks after treatment. All symptomatic cases were clinically cured. Conclusions: Serial serological determinations could be helpful for monitoring chronic schistosomiasis in non-endemic regions. The ideal timing for these follow-up tests is yet to be determined. Further research is needed to determine the factors that influence a negative result during follow-up.